2022
DOI: 10.5863/1551-6776-27.8.746
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Antibiotic Exposure for Suspected Early-Onset Sepsis in the Neonatal Intensive Care Unit Through Implementation of an Antimicrobial Time-out

Abstract: Antimicrobials are among the most frequently prescribed drugs in the neonatal intensive care unit (NICU), although most neonates exposed lack a bacterial infection. Overuse of antimicrobials carries risk to the patient and fosters the development of resistant organisms. Strategic and systematic processes hold promise to limit the unnecessary use of these drugs in this population. This study reports a quality improvement initiative in which 2 antimicrobial stewardship strategies were implemented in a large, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Other authors confirmed these results in early onset sepsis, suggesting that implementing an ASO is achievable by designing specific order sets within existing electronic medical record systems. These measures should be simple to implement and apply in most NICU settings [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Antimicrobial Time Out and Automatic Stop Order (Es 48 H)mentioning
confidence: 99%
“…Other authors confirmed these results in early onset sepsis, suggesting that implementing an ASO is achievable by designing specific order sets within existing electronic medical record systems. These measures should be simple to implement and apply in most NICU settings [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Antimicrobial Time Out and Automatic Stop Order (Es 48 H)mentioning
confidence: 99%